A high calorie diet induces type 2 diabetes in the desert sand rat (Psammomys obesus) - El Aoufi, S.; Gendre, P.; Sennoune, S.R.; Rigoard, P.; Maixent, J.M.; Griene, L. (Cellular and Molecular Biology, 2007)
Diabetes mellitus type 2 is a major factor for cardiovascular diseases. The toxic effects of chronic hyperglycemiainvolve many alterations in the vascular tissue, including atherosclerosis. The pathogenesis of atherosclerosis in the diabeticsyndrome (DS-II) has not been fully elucidated. A better understanding of the progress of DS-II at the level of the aortacould help us to identify inhibitors of atherosclerosis. Studies have shown that obesity and high calorie diet (HCD) areassociated with the development of DS-II, however the lack of naturally occurring experimental models of DS-II haveimpaired to directly address these issues. We hypothesize that a HCD induces DS-II. This study (15 months duration) isdesigned to determine if HCD induces DS-II in the desert sand rat (Psammomys obesus; P. obesus). We also evaluated thehistopathology of the aorta in animals fed with a laboratory chow pellets ad libitum (hypercaloric) and in control (animalsfed with the naturally occurring hypocaloric diet; halophile plants). The weight and blood chemistry (glucose, lipids, andinsulin levels) were evaluated periodically (once per week), and the histology of the aortas of these animals were assessedevery 3 months for up to 12 months, during the development of DS-II. This study demonstrates that 40% of the animals inHCD develop DS-II at 3 months. Histological characterization demonstrates the typical alterations observed inatherosclerosis, i.e., alteration of the elastic fibers of the media layer and enrichment in collagen and glucosaminoglycans.This study demonstrates that P. obesus is an excellent animal model to study the progression of DS-II and the developmentof atherosclerosis.